Validation of the Driving Cognitions Questionnaire (DCQ) for general Spanish population - Ruiz-García, Antonio; Wallace-Ruiz, Agustín; Jiménez, Óliver; Valero-Aguayo, Luis (Anales de Psicología / Annals of Psychology, 2026)
The Driving Cognitions Questionnaire (DCQ; Ehlers et al., 2007) assesses social concerns, accidents and panic attacks in cases of driving phobia. This phobia has a prevalence between 2% and 6%, and disables the person to drive or to do so with great anxiety. A study is presented on the psychometric characteristics of the DCQ adapted to the Spanish population. A total of 716 people participated (55.6% women), with a mean age of 37.7 years, with a range between 18 and 80 years, where 41.8% of them reported having had some negative experience when driving. The DCQ showed high internal consistency reliability (between α = .92 and .97) and test-retest reliability (between α = .73 and .87), as well as high convergent validity with the ISAT-3 questionnaire (between r = .72 and .80). The exploratory factor analysis showed the three factors, while the confirmatory factor analysis showed a model with two factors and another with three factors. We conclude on the usefulness of the DCQ for the assessment of driving phobia and anxiety, with a cut-off point of 52 as a criterion for considering intervention, in addition to the confirmation of the three factors.